Improving Estimation of Labor Market Disequilibrium through Inclusion of Shortage Indicators - Matthew Baird; Lindsay Daugherty; Krishna Kumar (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2017)
While economic studies assume that labor markets are in equilibrium, there may be specialized labor markets likely in disequilibrium. We develop a new methodology to improve the estimation of a reduced form disequilibrium model from the existing models by incorporating survey-based shortage indicators into the model and estimation. Our shortage indicator informed disequilibrium model includes as a special case the foundational model of Maddala and Nelson (1974), off of which we build. We demonstrate the gains in information provided by the methodology. We show how the model can be implemented by applying it to the market for anesthesiologists in the United States using two waves of surveys of anesthesiologists. In this application, we find that our new shortage indicator informed disequilibrium model fits the data better than the Maddala and Nelson model, as well as performing better with regards to out-of-sample predictive power.
Keywords: 330; Disequilibrium; labor; maximum likelihood; shortage; health provide